Doing your research project : a guide for first time researchers - Bell, Judith, 1930-; Waters, Stephen (Maidenhead, Berkshire McGraw-Hill Education, 2014)
This is the market leading book for anyone doing their research project. Clear, concise and extremely readable, this book provides a practical, step-by-step guide to doing a research project from start to finish. Thoroughly updated but retaining its well-loved style, this 6th edition includes: information on using online surveys; information on online interviewing and using online platforms for observation, e.g. Skype, Google Hangouts; new chapter on the use of social media in small scale research; thoroughly updated chapter on literature searching; revised and additional pedagogy; and a brand new text design. This practical, no-nonsense guide is vital reading for all those embarking on undergraduate or postgraduate study in any discipline, and for professionals in such fields as social science, education and health.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Education -- Research; Education -- Research -- Methodology; Social sciences -- Research; Social sciences -- Research -- Methodology; Independent study